Los factores psicosociales en Niños Entre 5 y 9 Años en Zona Rural del Municipio de Soacha - Cundinamarca (2022)
The research work shows us an overview of the psychosocial factors that are elements that can lead a child to present episodes, they can recognize them through school, social and family. The Analysis of Psychosocial Risks of 2018, carried out by the Observatory of the Police Family of the Directorate of Social Welfare, there were 100 cases of psychosocial risk in the 5 schools, with an increase of 50% compared to last year, this being frequent report since it is done once a year to determine if it continues to increase. In the city of Bogotá, a fundamental tool for collecting information is being carried out: the questionnaire; Q-PAD Problem Assessment to identify rates of body dissatisfaction, anxiety, substance abuse, interpersonal problems, family problems, future uncertainty, psychosocial risk, and selfesteem; and the academic performance reported by the schools, of a qualitative research type, was carried out in three schools in the city of Bogotá attached to the National Police, students from 5th to 12 years old, the results stated were that the students have a 70% risk psychosocial regarding academic performance, family. Taking into account these antecedents, this proposal proposes as a general objective; To identify the psychosocial factors in the family, school and social spheres, to which the students of a group of children from 5 to 9 years old located in the rural area of the municipality of Soacha are exposed, in this sense, the present investigation is part of qualitative studies, using narrative as a data collection strategy, through in-depth interviews. In accordance with the above, nonprobabilistic sampling, of the intentional type, is proposed as a strategy for selecting participants by Salinas Martínez (2004, p. 122) "Non-probabilistic sampling, also known as convenience sampling, and its only requirement is to meet the quota of the required number of subjects or observation units. In this, the probability of selection is unknown”; The main findings are that, through the interview with parents and students, it was possible to identify 11 some elements, particularly the family and the school, which, in particular cases, can lead to a minor presenting a psychosocial risk.